SWIMMING AS MEDIATOR IN THE SPORT OF INCLUSION IN AN ENVIRONMENT EXCLUSIVE (Fiep Bulletin - online, 2011)
This article focuses on the "social inclusion of physical disabled in high performance sport", presenting proposals that value the participation of physical and mentally disabled people in practice the sport of swimming to respect the values and concepts linked to the sport of competition, as well as insert the physical disabled in areas considered exclusive. The transmission of values through the sport, according to Sage (1980) and Barber (1982), are important components of the socialization process.Therefore the inclusion of physical disabled in these competitions in a competitive society includes aspects related to the merits of the gold medal. Through a project of social inclusion and culture innovation through competition in adapted sports, it is argued here the inclusion of the physical and mentally disabled in a new concept of values, such as: Social, religious, scientific, moral, ethical and behavioral.
Keywords: Physical and Mentally Disabled; Adapted Sports; Social Inclusion; Social Values